PRESSURE-BASED 3D CURVE DRAWING - LAI, CHAN YET (2014)
3D curve drawing is a fundamental operation in the creation and manipulation of surfaces and 3D models. Recent researches in 3D curve specification have ventured into specifying 3D curve through 2D sketched curves. Although techniques for specifying 3D curves using 2D input devices have been developed extensively, they are mostly expensive (due to the hardware required) and indirect, with the need of multiple viewpoints or multiple lines to specify a 3D curve. Pen pressure is an input channel typically available in tablet pen device. The use of pressure is natural, familiar and straightforward as it can be directly related to the context of varying pen, pencil or brush pressure to control the thickness of the drawn stroke, opacity or transparency of the paint colour. To date, little work has been done onusing pressure for 3D curve drawing as it is difficult to control pressure through a pressure sensitive pen. The amount of pressure perceived by human is not the same as the amount of pressure level sensed by digital instrument.